The Effect Of Higher Order Thinking Skill (HOTS) on Students’ Explanatory Text at SMA Negeri 2 Raha - Ocktavia, Young Ervina; Hanna, Hanna; Muhsin, Muhammad Khusnun (Journal of Teaching of English, 2022)
The objective of this research is to find out Higher Order Thinking Skill (HOTS) has significant effect on students’ writing explanatory text at SMAN 2 Raha. This research used pre experiment design One-Group Pretest-Posttest Design of class. The population of this research was all eleventh grade students in SMAN 2 Raha who registered on academic years 2019/2020 which were 488 students, while the subject of this research were students at class XI MIA1 which consisted of 40 students, but only 25 students were participated. The research instrument was written test which focus on explanatory text. The researcher collected data by provided pre-test, gave the treatment by applying Higher Order Thinking Skill (HOTS), and gave the post-test. The data was analyzed by using SPSS 16.0 version. To examine the hypothesis, the researcher used a paired sample t-test. Based on the result finding, writing explanatory text help students’ on developing their Higher Order Thinking Skill. Writing explanatory text acquired students a great deal of content knowledge before beginning the explanation. Students should be writing detailed and explained sequences of event. In addition, students expect to think critically to showed how and why something happen. Therefore, writing explanatory text has significant effect on students’ higher order thinking skill (HOTS).